Molecular Basis of Resistance to Macrolides and Other Antibiotics in Commensal Viridans Group Streptococci and Gemella spp. and Transfer of Resistance Genes to Streptococcus pneumoniae - Zolezzi, Paula Cerdá (American Society for Microbiology, 2004)
We assessed the mechanisms of resistance to macrolide-lincosamide-streptogramin B (MLS(B)) antibiotics and related antibiotics in erythromycin-resistant viridans group streptococci (n = 164) and Gemella spp. (n = 28). The macrolide resistance phenotype was predominant (59.38%); all isolates with this phenotype carried the mef(A) or mef(E) gene, with mef(E) being predominant (95.36%). The erm(B) gene was always detected in strains with constitutive and inducible MLS(B) resistance and was combined with the mef(A/E) gene in 47.44% of isolates. None of the isolates carried the erm(A) subclass erm(TR), erm(A), or erm(C) genes. The mel gene was detected in all but four strains carrying the mef(A/E) gene. The tet(M) gene was found in 86.90% of tetracycline-resistant isolates and was strongly associated with the presence of the erm(B) gene. The cat(pC194) gene was detected in seven chloramphenicol-resistant Streptococcus mitis isolates, and the aph(3′)-III gene was detected in four viridans group streptococcal isolates with high-level kanamycin resistance. The intTn gene was found in all isolates with the erm(B), tet(M), aph(3′)-III, and cat(pC194) gene. The mef(E) and mel genes were successfully transferred from both groups of bacteria to Streptococcus pneumoniae R6 by transformation. Viridans group streptococci and Gemella spp. seem to be important reservoirs of resistance genes.